Blends of Pereskia aculeata Miller mucilage, guar gum, and gum Arabic added to fermented milk beverages. (June 2018) - Amaral, Tatiana Nunes; Junqueira, Luciana Affonso; Prado, Mônica Elisabeth Torres; Cirillo, Marcelo Angelo; de Abreu, Luiz Ronaldo; Costa, Fabiano Freire; de Resende, Jaime Vilela
Abstract: Fermented milk products can be produced with hydrocolloids, such as guar gum (GG) and gum arabic (GA), to maintain quality during shelflife and to replace fat. Because of increasing demand for new hydrocolloids, Pereskia aculeata Miller (ora-pro-nobis; OPN) mucilage extract was prepared and may be a potential additive (gelling agent and/or emulsifier). One mixture design was used in model solutions, composed of OPN mucilage, GA, GG, sucrose, sodium chloride, and deionized water. The aim was to test rheological properties for all the treatments, and according to the results, to identify a suitable hydrocolloid blend to be added to fermented milk beverages (FMBs). The highest values of apparent viscosity of the model solutions were observed in the range where the hydrocolloid mix was composed of 70% OPN mucilage, 0% GA, and 30% GG, resulting in 0.5–0.7 Pa⋅s. Sucrose showed a greater influence on apparent viscosity than sodium chloride did. The effects of apparent viscosity, G′, and G″ were discussed, and the model solutions revealed pseudoplastic behavior with a good fit to the power law rheological model. FMB samples appeared to conform to the power law, pseudoplastic and thixotropic behavior, and predominant elastic behavior (G'>G"). Addition of hydrocolloid blends increased pH, protein content, apparent viscosity, firmness, and adhesiveness and reduced syneresis of the FMB. Fat content influenced the texture parameters, and the microstructure was visualized and supported the results. Application of hydrocolloid blends containing OPN mucilage seems to be worthwhile and increases the protein content of FMBs. Graphical abstract: Image 1 Highlights: Mucilage from Peréskia aculeata Miller (OPN) was tested in hydrocolloid blends. Hydrocolloid blends with OPN were applied in Fermented Milk beverages (FMB). Blends with OPN increased the viscosity, firmness and protein contents in FMB. Syneresis in FMB was reduced by hydrocolloids and was not influenced by milk fat. FMB with hydrocolloids blends with OPN proved to be a viable approach.